2020
DOI: 10.1155/2020/3176375
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Therapy under Hypoxic Microenvironment by the Combination of 2-Methoxyestradiol and Sodium Dichloroacetate on Human Non-Small-Cell Lung Cancer

Abstract: A hypoxic microenvironment is a hallmark in different types of tumors; this phenomenon participates in a metabolic alteration that confers resistance to treatments. Because of this, it was proposed that a combination of 2-methoxyestradiol (2-ME) and sodium dichloroacetate (DCA) could reduce this alteration, preventing proliferation through the reactivation of aerobic metabolism in lung adenocarcinoma cell line (A549). A549 cells were cultured in a hypoxic chamber at 1% O2 for 72 hours to determine the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Excluding the EGFR-addiction context, DCA was tested in addition with 2-methoxyestradiol (2-ME), a metabolite reducing angiogenesis, replication, and HIF-1α pathway in human tumour cell-lines. The combination exhibited promising anti-tumour effects in preclinical A549 NSCLC cell lines [ 340 ]. Current clinical data available on DCA explored its anti-tumour properties in a phase II trial, including 6 patients with NSCLC (and 1 patient with breast cancer).…”
Section: Hypoxia-related Treatments and Research Developmentmentioning
confidence: 99%
“…Excluding the EGFR-addiction context, DCA was tested in addition with 2-methoxyestradiol (2-ME), a metabolite reducing angiogenesis, replication, and HIF-1α pathway in human tumour cell-lines. The combination exhibited promising anti-tumour effects in preclinical A549 NSCLC cell lines [ 340 ]. Current clinical data available on DCA explored its anti-tumour properties in a phase II trial, including 6 patients with NSCLC (and 1 patient with breast cancer).…”
Section: Hypoxia-related Treatments and Research Developmentmentioning
confidence: 99%
“…Similarly to our studies on NSCLC cell models, according to the available data, sulfamoylated analogs of 2-ME, which influence the proliferation of MCF-7 and MDA-MB-231 breast cancer cells, were investigated in the study of the role of ROS in breast cancer [ 61 ]. These studies showed that sulfamoylated estradiol induced generation of superoxide anion and hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic glycolysis was ameliorated in DCA-treated A549 and H1299 cells, with decreased lactate generation and glucose consumption ( Allen et al, 2015 ). The combination of angiogenesis inhibitor 2-methoxyestradiol (2-ME) with DCA showed synergistic anti-tumor effects in A549 cells by reducing the signaling transduction of HIF-3α and, partially, of HIF-1α ( Romero et al, 2020 ). The combination of the energy metabolism inhibitor 3-bromopyruvate (3-BrPA) with the mTOR inhibitor rapamycin synergistically suppressed cell growth in H1299 and H23 cell lines and tumor growth in an A/J mouse model, respectively, indicating the promising therapeutic potential of both mTOR signaling and glycolysis inhibition in NSCLC ( Zhang et al, 2015 ).…”
Section: Current Treatments and Candidates Targeting Glycolysis In Nsclcmentioning
confidence: 99%